(untitled) (Computer systems and information technologies, 2022)
mandatory step, which is carried out to confirm the correctness, feasibility and feasibility of the developed solutions, including architecture, method of maintaining system integrity. In order to conduct a study on the effectiveness of the use of self-organized distributed systems, anomalies in computer systems were identified in relation to the evaluation criteria. Determining the specifics of the application of the system also affects the choice of criteria for evaluating effectiveness. The method of determining the effectiveness of the proposed solutions for the developed self-organized distributed system for detecting anomalies in computer systems has been developed. Software has been developed to ensure the functioning of a self-organized distributed anomaly detection system in computer systems to confirm the feasibility of the proposed solutions. Experimental studies with the developed implementation of a self-organized distributed system for detecting anomalies in computer systems according to the obtained coefficients confirmed the effectiveness of the proposed solutions and the developed distributed system for its operation in the computer network.